2015
DOI: 10.1016/j.bbadis.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Mild hypoxia in vivo regulates cardioprotective SUR2A: A role for Akt and LDH

Abstract: High-altitude residents have lower mortality rates for ischaemic heart disease and this is ascribed to cardiac gene remodelling by chronic hypoxia. SUR2A is a cardioprotective ABC protein serving as a subunit of sarcolemmal ATP-sensitive K+ channels. The purpose of this study was to determine whether SUR2A is regulated by mild hypoxia in vivo and to elucidate the underlying mechanism. Mice were exposed to either 21% (control) or 18% (mild hypoxia) oxygen for 24 h. Exposure to 18% oxygen did not affect partial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 33 publications
(68 reference statements)
0
39
0
Order By: Relevance
“…The sulfonylurea receptor 2A (SUR2A) is an ‘atypical’ ABC transporter that, although possessing a structure of an ABC protein, it does not mediate transport, but binds to the inward rectifier Kir6.2 to form sarcolemmal K ATP channels . Recent studies showed the involvement of SUR2A in regulation of myocardial resistance to metabolic and oxidative stress and to cardiac ageing . It has been shown that increased level of SUR2A ( i ) protects myocardium against ischaemia‐reperfusion and other types of oxidative stress , ( ii ) increases physical endurance , ( iii ) counteracts ageing‐induced increase in myocardial susceptibility to metabolic stress and decrease in physical endurance and ( iv ) reprogrammes embryonic cardiomyocytes towards less differentiated stem‐like cells .…”
Section: Introductionmentioning
confidence: 99%
“…The sulfonylurea receptor 2A (SUR2A) is an ‘atypical’ ABC transporter that, although possessing a structure of an ABC protein, it does not mediate transport, but binds to the inward rectifier Kir6.2 to form sarcolemmal K ATP channels . Recent studies showed the involvement of SUR2A in regulation of myocardial resistance to metabolic and oxidative stress and to cardiac ageing . It has been shown that increased level of SUR2A ( i ) protects myocardium against ischaemia‐reperfusion and other types of oxidative stress , ( ii ) increases physical endurance , ( iii ) counteracts ageing‐induced increase in myocardial susceptibility to metabolic stress and decrease in physical endurance and ( iv ) reprogrammes embryonic cardiomyocytes towards less differentiated stem‐like cells .…”
Section: Introductionmentioning
confidence: 99%
“…GAPDH could regulate KATP channels activity independent of high intracellular ATP by producing 1,3-bisphosphoglycerate [12][13][14][15]. Furthermore, this study is demonstrated slight but no significant effect of silencing GAPDH on cellular energy as measured by ATP.…”
Section: Discussionmentioning
confidence: 51%
“…It has been previously established that GAPDH is linked with cytoprotection in H9C2 cells by being part of the sarcolemmal ATP-sensitive K + (K ATP ) channels protein complex which is composed of Kir6.2 and SUR2A subunits, where it regulates channels activity irrespective of high intracellular ATP by producing 1,3-bisphosphoglycerate [12,13]. Also, both mild and severe hypoxia up-regulates SUR2A, which is known to increase levels of fully assembled K ATP channels and subsarcolemmal ATP in H9C2 cells [14][15][16]. An increase of K ATP channels http://dx.doi.org/10.1016/j.ijbiomac.2015.08.028 0141-8130/© 2015 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, another interesting protein which is upregulated by hypoxic conditions was described in two recently published studies by Mohammed Abdul et al [29,30]: the SUR2A (sulfonylurea receptor 2A) protein. SUR-proteins are regulatory elements of the K ATP -channel.…”
Section: Introductionmentioning
confidence: 99%
“…These ATP (adenosine triphosphate) sensitive potassium channels are composed of SUR1, SUR2A, or SUR2B subunits together with K ir 6.1 or K ir 6.2 depending on the tissue where they are expressed. In the heart, it was demonstrated that the expression of SUR2A is increased under hypoxic conditions and that this increase was accompanied by an improved survival of cardiomyocytes [29,30]. In the brain, the subunit SUR1 is co-expressed with K ir 6.x, and in experimental models of stroke it was demonstrated that blockade of SUR was associated with reduced infarct size and reduced cerebral edema [31,32].…”
Section: Introductionmentioning
confidence: 99%